Securitisation of Ukrainian Critical Infrastructures: The Case of the Failure of SCADA System in Protecting the Power Grids - Dini Putri Saraswati; Nurfarah Nidatya; Muhammad Kamil Ghiffary Abdurrahman (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Critical infrastructures are the important element to support the social cohesion in a certain area. Therefore, it is necessary to protect critical infrastructures in order to maintain the sustainability of the assets. There are many attempts of states to control the security of their critical infrastructures, one of them is using Supervisory Control and Data Acquisition (SCADA) system, a control system in which to monitor and retrieve data under the supervision of an operator. However, although countries are aware of the preventive action over their critical infrastructures, it is still possible to fail. In this case, Ukraine which has a relatively secure control system was failed in protecting its power grids from multiple hacker attacks which contributed to blackouts in December 2015. The devastating failure of Ukraine’s security system has led public opinion to point a finger to Russia since the relationship of both countries is at stake. In this sense, Ukraine issued a speech act to securitise its critical infrastructures. By exercising securitisation theory, this article would discuss further about the fruitfulness of the speech act after the failure of the security system in protecting Ukraine’s power grids.